Masked, diluted and drowned out: how global seafood trade weakens signals from marine ecosystems. Issue 4 (14th February 2015) - Crona, Beatrice I; Daw, Tim M; Swartz, Wilf; Norström, Albert V; Nyström, Magnus; Thyresson, Matilda; Folke, Carl; Hentati‐Sundberg, Jonas; Österblom, Henrik; Deutsch, Lisa; Troell, Max
Abstract: Nearly 40% of seafood is traded internationally and an even bigger proportion is affected by international trade, yet scholarship on marine fisheries has focused on global trends in stocks and catches, or on dynamics of individual fisheries, with limited attention to the link between individual fisheries, global trade and distant consumers. This paper examines the usefulness of fish price as a feedback signal to consumers about the state of fisheries and marine ecosystems. We suggest that the current nature of fisheries systems and global markets prevent transmission of such price signals from source fisheries to consumers. We propose several mechanisms that combine to weaken price signals, and present one example – the North Sea cod – to show how these mechanisms can be tested. The lack of a reliable price feedback to consumers represents a challenge for sustainable fisheries governance. We therefore propose three complimentary approaches to address the missing feedback: (i) strengthening information flow through improved traceability and visibility of individual fishers to consumers, (ii) capitalizing on the changing seafood trade structures and (iii) bypassing and complementing market mechanisms by directly targeting citizens and political actors regarding marine environmental issues through publicity and information campaigns. These strategies each have limitations and thus need to be pursued together to address the challenge of sustainability in global marine fisheries.